FAKTOR-FAKTOR PENYEBAB KEGAGALAN KELOMPOK TANI DAN UPJA MENINGKATAN LABA USAHA TANI (Factors Causing Failure Of Kelompok Tani And UPJA Increase Farm Profits) - Siti Nurhidayati Romadhoni; Sri Hanggana (Riset Manajemen dan Akuntansi, 2019)
This study aims to analyze the factors that cause farmers group (Poktan) and Agricultural Machinery and Equipment Service Business (UPJA) to fail to increase farm profits. The study was conducted with literature studies and strengthened with case studies. The data obtained were analyzed to identify the causes of failure in terms of regulation and actors. Factors causing failure from the regulatory side include Poktan membership status is not clearly regulated, the type of Poktan organization is not clearly regulated as a social organization or business organization, Poktan assistance from the government to the UPJA is not clearly regulated, insufficient, rental prices are not cheaper, the rights and obligations of the management and members of UPJA are unclear. The case study of UPJA Desa Sentana which received tractor assistance from the government can be concluded that the factors causing the failure of UPJA were that tractor rental prices were the same as market prices, had tractor subscriptions that yielded satisfactory results, non-sense members owned UPJA tractors, and members did not like management or operator. The implication of this study is that the government must establish new regulations that can serve as guidelines for membership status of Poktan and establish regulations that determine the type of organization of Poktan as social or business organizations. In addition, the Government also has to issue new regulations that can be a guideline in determining Alsintan's assistance to UPJA so that it can meet the needs of members and clearly regulate UPJA business management.